2014
DOI: 10.1134/s1990341314010015
|View full text |Cite
|
Sign up to set email alerts
|

Ionized gas rotation curves in nearby dwarf galaxies

Abstract: Abstract. We present the results of study of the ionized gas velocity fields in 28 nearby (systemic velocity below 1000 km s −1 ) dwarf galaxies. The observations were made at the 6-m BTA telescope of the SAO RAS with the scanning Fabry-Perot interferometer in the Hα emission line. We were able to measure regular circular rotation parameters in 25 galaxies. As a rule, rotation velocities measured in H II are in a good agreement with the data on the H I kinematics at the same radii. Three galaxies reveal positi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…The final angular resolution corresponds to a seeing of 1. 8 in comparison to Moiseev (2014) and Moiseev et al (2015) with deeper data but with a worse 2. 7 resolution.…”
Section: Bta Datamentioning
confidence: 86%
“…The final angular resolution corresponds to a seeing of 1. 8 in comparison to Moiseev (2014) and Moiseev et al (2015) with deeper data but with a worse 2. 7 resolution.…”
Section: Bta Datamentioning
confidence: 86%
“…We constructed a rotation model of Ho II from the H i velocity field using the tilted-ring approximation adapted to dwarf galaxy kinematics (Moiseev 2014) with initial parameters for Ho II taken from Oh et al (2011) (we list them in Table 2) and then subtracted this model from the observed data cube. As a result, we have obtained the data cube that reflects the local motions caused by stellar feedback.…”
Section: Optical Fpi Observationsmentioning
confidence: 99%
“…We construct a rotation model of IC 2574 from the H i velocity field (moment 1) using the tilted-ring approximation adapted to dwarf galaxy kinematics (Moiseev 2014). The coordinates of the dynamical centre, the inclination and the initial value of the major axis position angle were adapted from Oh et al (2008), who performed a careful study of the H i kinematics of this galaxy.…”
Section: Construction Of a Circular Rotation Modelmentioning
confidence: 99%